Modelo de gestión administrativa para mejorar la competitividad del Bar-Karaoke “La Zona GR” cantón, La Mana, provincia Cotopaxi, Año 2023 - Narváez Ramírez, Gissela Estefanía (2023)
The main objective of the research was focused on designing an administrative management model to improve the competitiveness at the Bar-Karaoke "La Zona GR", La Maná Canton, Cotopaxi province, year 2023. For this reason, a mixed methodology was established by applying the types of research as: applied, field, and descriptive. In addition, the used methods were: analysis and synthesis. The data collection instruments were: the structured interview, survey, and scientific observation. The population that was immersed to the investigation was 28,517 people. For calculating the sample, a proportion of 149 people was obtained, who were considered for the application of the aforementioned instruments. The most relevant result showed that there was a great deficiency in the administrative management at the Bar-Karaoke "La Zona GR"; because the opinions of the employees are not considered when making decisions which are associated with their job. Moreover, there is not an organizational structure that delimits departmental responsibilities and functions; likewise, there are not policies at the company that are aimed at customer service, complaint handling or development of functions. In the same way, the staff that work in the company are not qualified to carry out some activities inherent to their position. Finally, there are not advertising aspects that allow the company to position itself objectively in the market, enhancing the levels of competitiveness with other organizations with the same economic activities.